A COMMENT ON THE US STUDENT LOAN SITUATION FROM A POST-KEYNESIAN PERSPECTIVE - Pereira Serra, Gustavo (Brazilian Keynesian Review, 2023)
This paper aims to contribute to the debate on the US student debt situation. First, it highlights the determination of labor earnings and economic activity as a function of macroeconomic conditions and the relevance of considering this endogeneity to analyzing student debt sustainability. Next, I present a background on student loans and the labor market in the US. Moreover, using a Minskyian framework, I argue that the current student debt situation can have adverse results on economic activity, although not leading to financial instability. Last, I comment on the student debt cancellation debate, proposing alternative policies with more progressive and lasting effects.